Pendekatan Konseling Behavior Dalam Mengembangkan Self Management Pada Siswa SMK Di Dunia Kerja - Nakita Augydia Lesmana; Yenti Arsini; Abdur Razak (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2024)
Vocational High School (SMK) is one form of formal education unit that organizes vocational education at the secondary education level as a continuation of Junior High School (SMP), MTs, or a continuation of recognized learning outcomes equivalent to SMP/MTs. SMKs are expected to produce job-ready graduates, but in reality, most of the open unemployment comes from SMKs. One of the developmental tasks of adolescents, especially vocational students, is the achievement of career maturity. Career maturity is an aspect that students need to have to support their future careers. Career maturity is an attitude and competence that plays a role in career decision making. Vocational students are required to be able to make the right career choices when they are faced with the majors process to choose certain career choices. One of the efforts to help vocational students in dealing with career maturity problems is through behavioral counseling services with Self Management techniques. This writing uses the literature review method, so the goal is how behavioral counseling with Self Management techniques helps vocational students in developing their career maturity.